Proceedings of the 3rd Asia Pacific International Conference of Management and Business Science (AICMBS 2019) 2020
DOI: 10.2991/aebmr.k.200410.025
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Corporate Governance Mechanism in Enhancing Firm Value

Abstract: This research aims to examine the influence of corporate governance mechanism to enhance firm value. The corporate governance mechanism uses three variables: managerial ownership, independent commissioner, and audit committee. The population of this research is manufacturing companies listed in the Indonesia Stock Exchange during the period of 2015-2018, from which 144 companies were selected as the sample. The hypothesis testing was conducted through multiple regression analysis. This research finds that audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The results of this study support the first hypothesis which states that managerial ownership has a positive effect on firm value. These results are in line with research conducted by Indriastuti et al, (2020) and Abbasi et al, (2012) which states that managerial ownership has a positive and significant effect on firm value, so that H1 is accepted.…”
Section: The Effect Of Good Corporate Governance Mechanism On Firm Va...supporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study support the first hypothesis which states that managerial ownership has a positive effect on firm value. These results are in line with research conducted by Indriastuti et al, (2020) and Abbasi et al, (2012) which states that managerial ownership has a positive and significant effect on firm value, so that H1 is accepted.…”
Section: The Effect Of Good Corporate Governance Mechanism On Firm Va...supporting
confidence: 90%
“…Managers who are also shareholders will of course align their interests as managers with their interests as shareholders. The research results of Indriastuti et al, (2020) showed that managerial ownership has a positive and significant effect on firm value. Based on the description above, the development of the hypothesis derived is: H1: Managerial ownership has a positive effect on firm value.…”
Section: Hypotheses Development Managerial Ownership and Corporate Va...mentioning
confidence: 98%
“…The study results by Putra (2023) show that the higher the level of independence of the board of commissioners, the stronger the oversight function of managers motivated by achieving their profits. This is supported by the study by Indriastuti et al (2020), who stated that because independent commissioners are thought to reduce agency conflicts, their proportion has a beneficial impact on business value (Bernhard & Veny, 2024;Hidayat & Muliasari, 2020). Thus, the presence of independent commissioners is expected to be able to supervise tax aggressiveness policies to consider investor interests still and comply with applicable tax regulations.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Therefore, the independent commissioner is needed to supervise the decisions and policies made by managers, especially in tax planning policies. According to Indriastuti et al (2020), a high proportion of independent commissioners is also accompanied by an increase in firm value as they are considered to minimize managers' conflicts of interest. Study findings by Bernhard & Veny (2024) and Hidayat & Muliasari (2020) also explain that the role of independent commissioners can reduce company tax aggressiveness.…”
Section: Introductionmentioning
confidence: 99%